Association of Mid- to Late-Life Blood Pressure Patterns With Risk of Subsequent Coronary Heart Disease and Death - Liu, Menghui; Zhang, Shaozhao; Chen, Xiaohong; Zhong, Xiangbin; Xiong, Zhenyu; Yang, Daya; Lin, Yifen; Huang, Yiquan; Li, Yuqi; Wang, Lichun; Zhuang, Xiaodong; Liao, Xinxue (Frontiers in Cardiovascular Medicine, 2021)
Background: The elevated blood pressure (BP) at midlife or late-life is associated with cardiovascular disease and death. However, there is limited research on the association between the BP patterns from middle to old age and incident coronary heart disease (CHD) and death. Methods: A cohort of the Atherosclerosis Risk in Communities (ARIC) Study enrolled 9,829 participants who attended 5 in-person visits from 1987 to 2013. We determined the association of mid- to late-life BP patterns with incident CHD and all-cause mortality using multivariable-adjusted Cox proportional hazards models. Results: During a median of 16.7 years of follow-up, 3,134 deaths and 1,060 CHD events occurred. Compared with participants with midlife normotension, the adjusted hazard ratio for all-cause mortality and CHD was 1.14 (95% CI, 1.04-1.25) and 1.28 (95% CI, 1.10-1.50) in those with midlife hypertension, respectively. In further analyses, compared with a pattern of sustained normotension from mid- to late-life, there was no significant difference for the risk of incident death (HR, 1.15; 95% CI, 0.96-1.37) and CHD (HR, 1.33; 95% CI, 0.99-1.80) in participants with a pattern of midlife normotension and late-life hypertension with effective BP control. A higher risks of death and CHD were found in those with pattern of mid- to late-life hypertension with effective BP control (all-cause mortality: HR, 1.24; 95% CI, 1.08-1.43; CHD: HR, 1.65; 95% CI 1.30-2.09), pattern of midlife normotension and late-life hypertension with poor BP control (all-cause mortality: HR, 1.27; 95% CI, 1.12-1.44; CHD: HR, 1.53; 95% CI, 1.23-1.92), and pattern of mid- to late-life hypertension with poor BP control (all-cause mortality: HR, 1.49; 95% CI, 1.30-1.71; CHD: HR, 1.87; 95% CI, 1.48-2.37). Conclusions: The current findings underscore that the management of elderly hypertensive patients should not merely focus on the current BP status, but the middle-aged BP status. To achieve optimal reductions in the risk of CHD and death, it may be necessary to prevent, diagnose, and manage of hypertension throughout middle age.